The Construction of Struggle in Gran Turismo (2023): A Roland Barthes’ Semiotic Analysis of Jann Mardenborough - M Valent Ghaza Arifaya (Jogjakarta Communication Conference (JCC), 2026)
This study aims to analyze the construction of the meaning of struggle as represented through the character of Jann Mardenborough in the film Gran Turismo (2023). As a form of mass communication media, film not only conveys narratives but also constructs meaning through visual and symbolic signs that embody social and ideological values. This research employs a descriptive qualitative approach using Roland Barthes’ semiotic analysis, which emphasizes three levels of signification: denotation, connotation, and myth. The data were collected through non-participant observation by repeatedly watching the film and selecting key scenes that represent the dynamics of the character’s struggle. The analysis focuses on visual elements, dialogue, and cinematic aspects that contribute to the construction of meaning. The findings reveal that Jann’s struggle is not constructed as a linear and heroic process, but rather as a complex and non-linear experience shaped by psychological limitations, social pressures, and systemic constraints. Furthermore, the film both reproduces and critiques dominant myths of success, particularly the assumption that hard work inevitably leads to success. Thus, struggle in this film is represented as a process characterized by contradiction, uncertainty, and identity negotiation. This study contributes to the development of film semiotics by offering a multidimensional perspective on the representation of struggle in popular media.